Preparation and properties of 4, 4′‐diphenylmethane diisocyanate blocking modified poly(propylene carbonate). Issue 3 (13th August 2012) - Pang, Sujuan; Xu, Nai; Xu, Guang; Pan, Lisha; Lin, Qiang; Wang, Xin
Abstract Poly(propylene carbonate) (PPC) is inferior in thermal stability and liable to incur thermal degradation, especially in the existence of residual bimetal catalyst. In this article, PPC containing residual catalyst was end‐capped with 4, 4′‐diphenylmethane diisocyanate (MDI) through melt compounding. The blends were characterized by infrared spectra, melt flow index (MFI), gel permeation chromatography (GPC), gel content measurement, thermogravimetric analysis, scanning electron microscopy, and tensile test. The effect of MDI on thermal stability, molecular weight, and tensile properties of PPC was studied. Thermal degradation kinetics of neat PPC and PPC+MDI blending samples was discussed with Friedman method. MFI, GPC, and gel content measurements showed that mainly end‐capping reaction was carried out on PPC chains when 0.1% of MDI was added. However, as the amount of MDI exceeded to 0.3%, end‐capping, chain‐extension, and crosslinking reactions were synchronously carried out on PPC. Results showed that the end‐capping, chain‐extension, and crosslinking reaction occurring between PPC and MDI could effectively inhibit the unzipping degradation even when the residual catalyst was not removed thoroughly. When the content of MDI reached 1.0%, the initial degradation temperatures (T‐5%) increased from 176.26°C for neat PPC to 259.56°C. As a result, the processing temperature range and processing time were largely extended, and the heat resistance of PPC was improved remarkably. Meanwhile, the tensile property of the modified PPC was enhanced obviously. It may be due to the fact that the molecular weight and gel content of PPC were increased with the increasing amount of MDI. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013